1986
DOI: 10.1177/0013164486463014
|View full text |Cite
|
Sign up to set email alerts
|

Using Test-Taking Strategies to Maximize Multiple-Choice Test Scores

Abstract: The study was designed to answer two questions: (1) Can cognitive strategies to increase testwiseness be taught? (2) Can the testwiseness strategies be generalized by students so they can improve their scores on examinations other than those measuring testwiseness? Fifty-four undergraduate education students served as subjects. The treatment consisted of a one-hour lecture/discussion presentation covering four cognitive strategies identified as comprising testwiseness. This was followed by a 48 item instrument… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 10 publications
1
22
0
1
Order By: Relevance
“…Some researchers in this area have qeveloped the construct (Carter, 1986;Engelhardt, 1979;Millman, 1966;Millmain et al, 1965;Rogers & Bateson, 199 1 ), and others have attempted to create instruments to assess individual testwiseness skills or abilities (Brown, 1964;Diamond & Evans, 1972;Gibb, 1964;Johnson, 1976;Millman, 1966). Researchers have also found that testwiseness skills introduce additional variance into examination scores (Cronbach, 1946;Fagley, 1987;Flynn &Anderson, 1977;Thorndike, 195 1) and that there is a positive association between testwiseness skills and classroom examination performance (Bruch, Juster, & Kaflowitz, 1983;Dolly & Williams, 1986;Fagley, Miller, & Downing, 1990).…”
mentioning
confidence: 99%
“…Some researchers in this area have qeveloped the construct (Carter, 1986;Engelhardt, 1979;Millman, 1966;Millmain et al, 1965;Rogers & Bateson, 199 1 ), and others have attempted to create instruments to assess individual testwiseness skills or abilities (Brown, 1964;Diamond & Evans, 1972;Gibb, 1964;Johnson, 1976;Millman, 1966). Researchers have also found that testwiseness skills introduce additional variance into examination scores (Cronbach, 1946;Fagley, 1987;Flynn &Anderson, 1977;Thorndike, 195 1) and that there is a positive association between testwiseness skills and classroom examination performance (Bruch, Juster, & Kaflowitz, 1983;Dolly & Williams, 1986;Fagley, Miller, & Downing, 1990).…”
mentioning
confidence: 99%
“…Students who have or acquire test-taking strategies or skills will positively affect their testing competence and, hence, their academic performance. This is particularly true for low-ability students who perform better than expected (Dolly and Williams 1986). On the other hand, students who are expected to do well in tests but do not either lack testing strategies or use poor ones (Vattanapath and Jaiprayoon 1999).…”
Section: Importance Of Test-taking Strategiesmentioning
confidence: 99%
“…Testwiseness exists independently of the knowledge a person has about a subject matter." (p. 2) Dolly and Williams (1986) state that testwiseness is " cognitive strategies used to maximize chances of selecting the correct option when the test taker was forced to guess due to lack of information concerning the content of an item." (p. 620) Essentially, a testwise student can navigate through a multiple choice test using testwise skills and succeed without knowing anything about the subject area being tested.…”
Section: Instructional Strategies Teachers Use To Preparementioning
confidence: 99%